Rancang Bangun Mesin Penepung Ubur - Ubur - Junaidi, J; Kurnianto, Rudi; Uslianti, Silvia; Wahyudi, Tri (ELKHA : Jurnal Teknik Elektro, 2015)
Abstract– Desa  Temajuk  located in  Kecamatan Paloh of Sambas District is one of the  villages  directly  borders to the Sarawak    (East Malaysia). Jellyfish is a marine commodities that considerable  potential in the  village.  Problem  faced by fishermen is the decline of the price of dried jellyfish that impacted on the income of the fishermen. The selling price of Jellyfish in 2012 is Rp.28.000.000/ton, whereas in 2013 the price dropped to Rp.17500000/ton. It is needed a jellyfish processing to increase the storage time, so that the selling price could be higher. This research aims is to design and build a flour making machine of jellyfish. The laboratory test results on the jellyfish flour contain 6,3%  of water, 4,9 of ash, 14,2% of crude fiber, 12,4% of fat, 82,2mg/L of potassium, 52,6mg/L of Phosphorus and 8,7% of NaCl. Keywords– Jellyfish, flour, machine, design and build.